Gene Expression and Structural Differences Underpinning Black and White Colouration in Spiders - Fabian C. Salgado‐Roa; Devi Stuart‐Fox; Laura Ospina‐Rozo; Iliana Medina (Molecular Ecology, 2026)
The presence of multiple color variants within a single population, known as color polymorphism, is a striking example of intraspecific phenotypic variation and a model for studying evolutionary processes. These processes depend on the underlying mechanisms such as the genes and pigments involved; but we currently lack such information for non‐model groups such as arachnids. We examined the genes associated with color polymorphism in the Australian Christmas spider, Austracantha minax , a widespread species with two female‐restricted color morphs: one that is completely black and the other presenting a black‐and‐white pattern on its dorsum. We sequenced the mRNA of individuals of both morphs at different developmental stages and assessed differences in gene expression between color morphs based on a de novo transcriptome assembly for the species, and integrated this with high resolution electron microscopy observations. We found that gene expression patterns are primarily influenced by the stage of development, and within each stage we found differentially expressed genes between the black and black‐and‐white morphs, especially in the adult stage. Contrary to expectations, these genes were not associated with melanin or guanine crystal deposition (detected in the microscopy), but were associated with chitin and cuticle metabolic processes. By exploring arachnid coloration at the transcriptomic level, our work reveals for the first time genetic mechanisms underpinning the evolution of color polymorphism in spiders.

Body size rather than reflectivity explains thermal constraints on colour variation in an aposematic jewel bug - Kei-Lin M. Ooi; Iliana Medina; Fabian C. Salgado-Roa; Devi Stuart-Fox (Evolutionary Ecology, 2025)
Theory posits that warning signals should converge phenotypically to reinforce predator memory, yet many aposematic species show substantial variation in warning signals within and between populations. This could be explained by alternative selective pressures on phenotype beyond predation such as thermoregulation, but empirical tests are scarce and do not consider the full spectrum of sunlight. To examine whether trade-offs with thermoregulation could explain variation in warning colouration, we examined thermal properties of colour variants of the aposematic cotton harlequin bug ( Tectocoris diophthalmus ). This species shows striking variation in warning signals: it is sexually dichromatic, varies within sexes, and shows clinal variation in colour frequencies, with iridescent blue-green colouration prevalent in cooler climates and non-iridescent red–orange colouration prevalent in warmer climates. We quantified reflectivity between colour variants over the full solar spectrum and investigated the contribution of ultraviolet and visible (UV–visible, 300–700 nm) and near infrared (NIR, 700–1700 nm) light on heating. Differences in reflectivity of iridescent and non-iridescent colour patches were greater in NIR than UV–visible wavelengths but did not result in significant differences in heating. However, we found a tight link between body size and reflectivity, with smaller males having lower reflectivity and heating faster. Due to the strong correlation between body size and colouration, thermal constraints related to body size may help to explain the observed clinal variation in colour frequencies.

Spatial preferences influence associations between magnitude and space in honey bees - Jung-Chun (Zaza) Kuo; Leslie Ng; Devi Stuart-Fox; Adrian G. Dyer; Scarlett R. Howard (Animal Behaviour, 2025)

A supermatrix phylogeny of the world’s bees (Hymenoptera: Anthophila) - Patricia Henríquez-Piskulich; Andrew F. Hugall; Devi Stuart-Fox (Molecular Phylogenetics and Evolution, 2024)

Which side are you on? Spider web positioning affects prey capture more than body colour - Fabian C. Salgado-Roa; Devi Stuart-Fox; Edwin Castañeda; Maira S. Tique Obando; Iliana Medina (Evolutionary Ecology, 2023)
Colour has been hypothesized to play a crucial role in prey capture for sit-and-wait predators that rely on visual cues to deceive their prey. Prey capture success has been directly linked to colouration in spiders; however, evidence so far focuses mostly on dorsal colouration, excluding ventral patterns that are visible to prey and may be relevant for prey attraction. Here, we explored whether the dorsal and ventral colouration of a colour polymorphic spider is associated with light environment and prey capture success. We quantified the number of prey captured across three dorsal (black, white, and yellow) and two ventral (black and a mosaic yellow/orange pattern) morphs of Gasteracantha cancriformis , considering light intensity on dorsal and ventral sides. We found that spiders capture more prey in low light environments, and that individuals often expose their dorsal colouration towards low light levels. We did not find significant differences in prey capture rate between morphs dorsally or ventrally. These results indicate that how and where spiders position their web can be more important for prey capture than colouration. Alternative hypotheses such as aposematism, camouflage and thermoregulation deserve more attention in future studies that aim to understand the role of colouration in spiders and the factors causing spider colour polymorphisms.

Disentangling thermal from alternative drivers of reflectance in jewel beetles: A macroecological study - Lu‐Yi Wang; Amanda M. Franklin; Andrew F. Hugall; Iliana Medina; Devi Stuart‐Fox (Global Ecology and Biogeography, 2023)
Aim To predict future colour–climate relationships, it is important to distinguish thermal drivers of reflectance from other evolutionary drivers. We aimed to achieve this by comparing relationships between climate and coloration in ultraviolet–visible (UV–Vis) and near‐infrared (NIR) light, separately. Location Samples were distributed primarily across Australia and North America, with some from Africa and Asia. Major taxa studied Coleoptera: Buprestidae. Methods We used jewel beetles as models to identify climatic drivers of reflectance, because jewel beetles have highly diverse coloration and a wide distribution and are often active in hot conditions. Specifically, we tested the association between climate, body size and reflectance using a phylogenetic comparative analysis for three wavebands (UV–Vis, NIR and total). Results Reflectance of jewel beetles was more strongly predicted by body size than by climate. NIR reflectance and total reflectance were not associated with climate, but larger beetles had higher NIR reflectance. For UV–Vis reflectance, small beetles were darker in warmer and more humid environments, whereas there was no association with climate for large beetles. Main conclusions Our study suggests that variation in reflectance of jewel beetles is not driven by thermal requirements and highlights the importance of considering NIR reflectance when evaluating explanations of the effects of colour on thermoregulation.

Environmental gradients predict the ratio of environmentally acquired carotenoids to self‐synthesised pteridine pigments - Devi Stuart‐Fox; Katrina J. Rankin; Adrian Lutz; Adam Elliott; Andrew F. Hugall; Claire A. McLean; Iliana Medina (Ecology Letters, 2021)
Carotenoids are important pigments producing integument colouration; however, their dietary availability may be limited in some environments. Many species produce yellow to red hues using a combination of carotenoids and self‐synthesised pteridine pigments. A compelling hypothesis is that pteridines replace carotenoids in environments where carotenoid availability is limited. To test this hypothesis, we quantified concentrations of five carotenoid and six pteridine pigments in multiple skin colours and individuals from 27 species of agamid lizards. We show that environmental gradients predict the ratio of carotenoids to pteridines; carotenoid concentrations are lower and pteridine concentrations higher in arid environments with low vegetation productivity. Both carotenoid and pteridine pigments were present in all species, but only pteridine concentrations explained colour variation among species and there were no correlations between carotenoid and pteridine pigments with a similar hue. These results suggest that in arid environments, where carotenoids are likely limited, species may compensate by synthesising more pteridines but do not necessarily replace carotenoids with pteridines of similar hue.

Climate predicts both visible and near‐infrared reflectance in butterflies - Changku Kang; Sehyeok Im; Won Young Lee; Yunji Choi; Devi Stuart‐Fox; Blanca Huertas (Ecology Letters, 2021)
Climatic gradients frequently predict large‐scale ecogeographical patterns in animal coloration, but the underlying causes are often difficult to disentangle. We examined ecogeographical patterns of reflectance among 343 European butterfly species and isolated the role of selection for thermal benefits by comparing animal‐visible and near‐infrared (NIR) wavebands. NIR light accounts for ~50% of solar energy but cannot be seen by animals so functions primarily in thermal control. We found that reflectance of both dorsal and ventral surfaces shows thermally adaptive correlations with climatic factors including temperature and precipitation. This adaptive variation was more prominent in NIR than animal‐visible wavebands and for body regions (thorax‐abdomen and basal wings) that are most important for thermoregulation. Thermal environments also predicted the reflectance difference between dorsal and ventral surfaces, which may be due to modulation between requirements for heating and cooling. These results highlight the importance of climatic gradients in shaping the reflectance properties of butterflies at a continent‐wide scale.

A test of an antipredatory function of conspicuous plastron coloration in hatchling turtles - Beth A. Reinke; Ryan Calsbeek; Devi Stuart-Fox (Evolutionary Ecology, 2017)

A complex history of introgression and vicariance in a threatened montane skink (Pseudemoia cryodroma) across an Australian sky island system - Margaret L. Haines; Devi Stuart-Fox; Joanna Sumner; Nick Clemann; David G. Chapple; Jane Melville (Conservation Genetics, 2017)

Rival assessment and comparison of morphological and performance-based predictors of fighting ability in Lake Eyre dragon lizards, Ctenophorus maculosus - Claire A. McLean; Devi Stuart-Fox (Behavioral Ecology and Sociobiology, 2015)

Processes driving male breeding colour and ecomorphological diversification in rainbow skinks: a phylogenetic comparative test - Gaynor Dolman; Devi Stuart-Fox (Evolutionary Ecology, 2010)

Sex steroid correlates of female-specific colouration, behaviour and reproductive state in Lake Eyre dragon lizards, Ctenophorus maculosus - Tim S. Jessop; Rita Chan; Devi Stuart-Fox (Journal of Comparative Physiology A, 2009)

A test of Rensch’s rule in dwarf chameleons (Bradypodion spp.), a group with female-biased sexual size dimorphism - Devi Stuart-Fox (Evolutionary Ecology, 2009)

Shouting the odds: vocalization signals status in a lizard - Toby J. Hibbitts; Martin J. Whiting; Devi M. Stuart-Fox (Behavioral Ecology and Sociobiology, 2007)